Gonchar V.A., Parshenko A.V., Donchenko T.V. Resistance of cut tool after ion nitriding in non-hydrogen inflammable environments. - Гончар, В. А.; Паршенко, А. В.; Донченко, Т. В. (Problems of Tribology, 2018)
The tool is a basic component of machine-building production, the quality and condition of which depends on the quality of manufactured products. The solution contributes to increasing the profitability and competitiveness of products and production in general. Promising methods of increasing the wear-resistance of the tool are the application of wear-resistant coatings by methods of deposition in vacuum, electrospray doping, chemical-thermal treatment in a plasma of glow discharge, laser heat treatment. Studies show that the most favorable in terms of durability and wear resistance is the gradient structure of the material with a smooth decrease in hardness over the depth of the layer from the surface to the core. We have developed technologies for strengthening the surfaces of the cutting tool by the method of applying diffusion coatings in the plasma of the glow discharge in non-aqueous media (a mixture of nitrogen and argon) and obtaining on the surface of tool steels and solid alloys of nitride phases. It was the use of anhydrous saturated environments in technological processes to exclude the hydrogen permeation of reinforced products and tools. Khmelnitsky National University has developed and operated equipment for processing in the glow discharge. For a more detailed study of the effect of the nitriding regime on the performance of the end mills, an experiment was conducted in which the wear of the teeth of conventional and reinforced mills was fixed on the back surface. The analysis of the obtained results shows that during the treatment of steel the wear of the teeth of the strengthened mills in comparison with the wear of conventional mills decreased by an average of 2 to 6 times. The use of ion nitriding to strengthen the metal cutting tool made from high-speed steels, with the correct selection of the nitriding regime, can increase the durability of the tool several times, which will increase the cost-effectiveness and efficiency of machine-building production.